FACTORS IMPROVING THE QUALITY OF ORGANIZATIONAL PERFORMANCE AT CV BUAHE BAROKAH - Santi, Fannisa Tiara; Kurniawan, Daniel; Sutrisno, Timotius F. C. W. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study aims to examine the effect of system of information management utilization on organizational performance mediated by knowledge management and employee engagement. The population in this study were employees of CV Buahe Barokah. The sampling technique used was saturated sampling. The questionnaire was distributed through an offline questionnaire to respondents who were employees of CV Buahe Barokah. This study obtained 73 samples that were eligible for analysis. The data were analyzed using Smart PLS software and using path analysis. The results of this study indicate that system of information management has an effect on organizational performance mediated by knowledge management and employee engagement of CV Buahe Barokah employees.